Molecular Mechanism of Alzheimer's Disease - Macreadie, Ian (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Alzheimer's disease (AD) is an age-related neurological disease that affects tens of millions of people, in addition to their carers. Hallmark features of AD include plaques composed of amyloid beta, as well as neurofibrillary tangles of tau protein. However, despite more than a century of study, the cause of Alzheimer's disease remains unresolved. The roles of amyloid beta and tau are being questioned and other causes of AD are now under consideration. The contributions of researchers, model organisms, and various hypotheses will be examined in this Special Issue.